Determinants of Digital Transformation in Improving Banking Service Quality: A Systematic Review (Al-Farooq Journal of Sciences, 2026)
This study aimed to analyze the determinants of digital transformation in improving banking service quality through a systematic review of the relevant academic literature. The importance of the study stems from the rapid expansion of digital technologies in the banking sector and the resulting fundamental changes in business models, service delivery methods, customer expectations, and competitive standards among financial institutions. The study adopted the systematic review method based on the principles of PRISMA 2020, by collecting published studies from recognized academic databases, screening them, and synthesizing their main findings in a structured manner. The findings revealed that the success of digital transformation in the banking sector does not depend solely on adopting technology itself, but rather on a set of interrelated internal and external determinants. The most significant internal determinants include technological infrastructure, top management support, strategic leadership, human resource capabilities, and an innovation-oriented organizational culture. External determinants include the regulatory and legislative environment, market competition intensity, the spread of financial technology, and the level of digital readiness in society. In addition, customer-related factors such as trust, perceived ease of use, perceived usefulness, and security were found to play a crucial role in the adoption and continued use of digital banking services. The study also showed that digital transformation significantly improves banking service quality by increasing transaction speed, enhancing reliability, enabling 24/7 service availability, improving customer experience, increasing satisfaction and loyalty, and reducing operational errors. However, several challenges may limit these positive effects, such as cybersecurity risks, resistance to change, high investment costs, and the digital divide among customer groups. The study concluded that improving banking service quality through digital transformation requires an integrated strategic vision that combines technology, human resources, organizational readiness, customer experience, and a supportive external environment. The study also provides a conceptual framework that can benefit researchers, decision-makers, and banking managers in designing more efficient and sustainable digital strategies.
Keywords: Digital Transformation, Banking Service Quality, Banking Sector, Systematic Review, Customer Experience